2015
DOI: 10.1186/2194-7791-2-s1-a3
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomic screening reveals asparagine dependence as a metabolic vulnerability in sarcoma

Abstract: This supplement has not been sponsored. Meeting abstracts Aims Rhabdomyosarcomas (RMS) are mesodermal malignancies with skeletal muscle differentiation. The most common oncogenic mutations in RMS are in the RAS pathway. This study sought to identify actionable gene targets in sarcomas by selective targeting of the molecular networks that support the growth of Ras-driven sarcomas in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 0 publications
3
49
1
Order By: Relevance
“…Nonetheless, and very importantly, ASNS inhibitor 1 (Fig. 1b) does negatively impact the growth of sarcoma cells in a manner similar to that seen when ASNS expression is reduced using siRNA knockdown methods 9 . Moreover, this compound is cytotoxic against asparaginase-resistant MOLT-4 leukemia cells when used at micromolar concentrations 21 .…”
mentioning
confidence: 58%
“…Nonetheless, and very importantly, ASNS inhibitor 1 (Fig. 1b) does negatively impact the growth of sarcoma cells in a manner similar to that seen when ASNS expression is reduced using siRNA knockdown methods 9 . Moreover, this compound is cytotoxic against asparaginase-resistant MOLT-4 leukemia cells when used at micromolar concentrations 21 .…”
mentioning
confidence: 58%
“…The importance of asparagine for tumor growth is highlighted by the fact that depletion of asparagine pools with L-asparaginase inhibits translation elongation and is used in treating low-ASNS-expressing acute lymphoblastic leukemia and pediatric acute myeloid leukemia (Hill et al, 1967). Moreover, ASNS expression is required for the survival of cultured glioma and neuroblastoma cell lines (Zhang et al, 2014), as well as for the growth of mouse sarcomas (Hettmer et al, 2015). Asparagine levels were also shown to function in the regulation of amino-acid uptake, and to positively regulate the expression of genes of the serine synthesis pathway (Krall et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting of the molecular network that support sarcoma cell proliferation identified actionable gene targets encoding enzymes relevant to amino acid biosynthesis: asparagine synthetase (ASNS), branched chain aminotransferase 1 (BCAT1), phosphoserine aminotransferase (PSAT1) and phosphoglycerate dehydrogenase (PHGDH) 62 . Silencing of ASNS, an amidotransferase that converts aspartate into asparagine, produced the strongest inhibitory effect on sarcoma growth in a functional genomic screen of mouse sarcomas generated by oncogenic KRAS and disruption of Cdkn2A.…”
Section: Bioenergetic Properties and Metabolic Vulnerabilitiesmentioning
confidence: 99%
“…These effects of ASNS silencing were reversed by exogenous supplementation with asparagine. Asparagine depletion via the ASNS inhibitor amino sulfoximine 5 (AS5) or asparaginase, inhibited mouse and human sarcoma growth in vitro, and genetic silencing of ASNS in mouse sarcoma cells combined with depletion of plasma asparagine inhibited tumor growth in vivo, as well 62 . A recent report demonstrated that asparagine can suppress cell death in glutamine-deprived cells 63 , implicating asparagine in promoting cellular adaptation to metabolic stresses such as glutamine depletion.…”
Section: Bioenergetic Properties and Metabolic Vulnerabilitiesmentioning
confidence: 99%